BRCA1 deficiency in mature CD8+ T lymphocytes impairs antitumor immunity. Issue 2 (2nd February 2023) - Wu, Bogang; Qi, Leilei; Chiang, Huai-Chin; Pan, Haihui; Zhang, Xiaowen; Greenbaum, Alexandra; Stark, Elizabeth; Wang, Li-Ju; Chen, Yidong; Haddad, Bassem R.; Clagett, Dionyssia; Isaacs, Claudine; et al.
Abstract : Women with BRCA1 germline mutations have approximately an 80% lifetime chance of developing breast cancer. While the tumor suppressor function of BRCA1 in breast epithelium has been studied extensively, it is not clear whether BRCA1 deficiency in non-breast somatic cells also contribute to tumorigenesis. Here, we report that mouse Brca1 knockout (KO) in mature T lymphocytes compromises host antitumor immune response to transplanted syngeneic mouse mammary tumors. T cell adoptive transfer further corroborates CD8 + T cell-intrinsic impact of Brca1 KO on antitumor adaptive immunity. T cell-specific Brca1 KO mice exhibit fewer total CD8 +, more exhausted, reduced cytotoxic, and reduced memory tumor-infiltrating T cell populations. Consistent with the preclinical data, cancer-free BRCA1 mutation-carrying women display lower abundance of circulating CD8 + lymphocytes than the age-matched control group. Thus, our findings support the notion that BRCA1 deficiency in adaptive immunity could contribute to BRCA1 -related tumorigenesis. We also suggest that prophylactic boosting of adaptive immunity may reduce cancer incidence among at-risk women.